Prediction of dynamics change in biowaste quantity collected in functionally different regions. A case study of Poland - Tałałaj, Izabela Anna; Hajduk, Sławomira; Wiszniewska, Anna (Economics and Environment, 2025)
The aim of the paper is to determine the dynamics of change in biowaste quantity as well as to forecast the amount of biowaste generated in 4 functionally different regions of Poland. The analysis was made for a period of 16 years (2007-2022), and a prognosis was made for the next 4 years (2023-2026). Based on the obtained data, the following calculations were made: share of biowaste from households in the quantity of total municipal biowaste, accumulation rate of biowaste from households, medium-term change rate in the amount of biowaste from households, and prediction of changes in the biowaste accumulation index until 2026. In all the analysed regions, an increasing trend in the collected biowaste mass index has been observed. The agricultural and recreational regions were characterised by the highest dynamics of changes in collected biowaste quantity (T=0.21 and 0.25, respectively) and by the lowest values of their accumulation indicator (48.9 and 44.7 kg/ca per year, respectively). The highest quantity of biowaste is predicted to be generated in urbanised and industrialised regions (62.1 and 53.2 kg/ca per year, respectively).